Analysis of the Impact of Brand Image, Brand Trust, and Brand Awareness on Brand Loyalty Toyota Car in Cirebon - Akyadi Akyadi; Isma Fazriyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The purpose of this research is to find out how much of an impact brand perception, trust, and knowledge have on Toyota customers' loyalty in Cirebon City. The method was quantitative, and it made use of a 4-point Likert scale, from (1) very disagree to (4) very agree. We want to reach out to everyone living in or around Cirebon City and the adjacent regency who drives a Toyota. The population size was not known, thus a sample size of 100 respondents was determined using the Lemeshow method and simple random sampling. Validity evaluations, multiple regression analysis, t-tests, F-tests, and the computation of the coefficient of determination were all part of the data analysis that was carried out using SPSS version 26. Brand awareness had the greatest impact on brand loyalty, with 62% (β = 0.622) of the total, followed by brand image at 41% (β = 0.401), and finally, brand trust at 14% (β = 0.147), according to the data. In addition, the results of the t-test show that brand awareness and brand image have a substantial influence on brand loyalty, but brand trust does not.